2015
DOI: 10.2139/ssrn.2616749
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Seeking Civil Justice in Canada

Abstract: How much does it cost individual Canadians to seek civil justice? This article compiles empirical data about the monetary, temporal, and psychological costs confronting individual justice-seekers in this country. The analysis considers the hourly rates of Canadian lawyers relative to American lawyers, and the costs confronting justice-seekers in family courts relative to other civil courts, among other topics. The article suggests that analysis of private costs can improve access to justice in two ways. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…They also found that the most filed cases were 'post-divorce' cases. Semple (2015) examined the private and health cost of civil justice. He conducted interviews of 250 litigants involved in different types of cases from Ontario, British Columbia, and Alberta.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also found that the most filed cases were 'post-divorce' cases. Semple (2015) examined the private and health cost of civil justice. He conducted interviews of 250 litigants involved in different types of cases from Ontario, British Columbia, and Alberta.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, researchers discussed monetary cost as well as nonmonetary cost. Semple (2015) examined the private cost of civil justice, the time required to solve cases of different nature, and health cost as well. For this purpose, he conducted interviews on 250 litigants which involved different types of cases from Ontario, British Columbia, and Alberta.…”
Section: Literature Reviewmentioning
confidence: 99%